Clinton and Trump: Two Faces of American Nationalism. Issue 5 (2nd September 2016) - Lieven, Anatol
Abstract : Donald Trump and Hillary Clinton exemplify new forms of old nationalisms that are likely to define politics in the United States for many years to come.